Dual responsive salen-type Schiff bases for the effective detection of l-arginine via a static quenching mechanism. (10th July 2018) - Mohan, Nithya; Sreejith, S. S.; Begum, P. M. Sabura; Kurup, M. R. Prathapachandra
Abstract : The effect of substituents of salen Schiff bases on the detection ofl -arginine via a static quenching mechanism is discussed. Abstract : l -Arginine is one of the most important amino acids and plays a key role in diagnostic studies. Herein, we report four salen-type Schiff base fluorimetric/colorimetric sensors for the rapid detection ofl -arginine. Substituents play a major role in the sensing mechanism of probes with the nitro-substituent bearing probe showing the highest efficiency. A 1 : 2 complexation between all the probes and the analyte was evidenced from the absorption titrations; and the fluorescence studies revealed a quenching phenomenon occurring during complex formation. From the life time measurements, the nature of quenching was found to be static and the formation of a ground state complex was confirmed. DFT calculations done at the B3LYP/TZVP level of theory corroborated the experimental findings and further established the proton transfer from the probe to the analyte during the complex formation.